Experience of Traditional Chinese Medicine enema and emergency care for 8 patients with acute drug poisoning (中药灌肠治疗药物中毒8例的护理体会) - ZHANG Tingting (张婷婷); ZHOU Jie (周洁); QIAO Xinli (乔新立); CHEN Hong (陈宏); TANG Ling (唐玲); WANG Jingjing (王晶晶) (中西医结合护理)
This paper summarized the experience of Traditional Chinese Medicine (TCM) enema and emergency care for 8 patients with acute drug poisoning. Based on the routine emergency management, TCM enema was adopted to relieve the symptoms of drug poisoning, prevent the complications, reduce mortality risk and improve the recovery of body function. (本文回顾中药灌肠治疗8例药物中毒患者的急救和护理措施。在常规急救治疗的基础上, 采用中药灌肠及中医特色护理干预可有效控制中毒症状, 对提高急救治疗效果、降低并发症和死亡风险、促进机体功能恢复具有积极意义。)